Case study of selecting decision-making schemes in large-scale infrastructure projects - Liang, R.; Dong, Z.; Sheng, Z.; Wang, Xiangyu; Wu, C. (American Society of Civil Engineers, 2017)
How to select decision-making schemes is a major concern in large-scale infrastructure projects. This paper proposes a new approach for this selection problem, which integrates collaborative information with individual information focusing on the linguistic variables of experts. It also applies an extended fuzzy technique to order preference by similarity to ideal solution (TOPSIS), to determine the fuzzy positive-ideal solution (FPIS) and the fuzzy negative-ideal solution (FNIS), and to rank the order of all alternative schemes through calculating the relative closeness of each alternative scheme to the FPIS and FNIS. A case study of Hong Kong-Zhuhai- Macao-Bridge (HZMB) project in China is used to demonstrate how to apply this approach and what its advantages are. Compared to the existing methods, this proposed method can produce reasonable solutions for real-world practice.